2007
DOI: 10.1002/ejic.200700118
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Triaquatricarbonylrhenium(I) Cation and Its Conjugate Base

Abstract: The crystal structure of the Re(CO) 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…One equivalent each of the rhenium reagent and sodium dimethyldithiocarbamate hydrate and an excess of the neutral ligand were allowed to reflux in the solvent. It made no difference in outcome whether Re(CO) 5 3 ]Á6H 2 O [28]) was used as the reagent. Previously, we found that Re(CO) 3 L 3 + (L = NH 3 , tetrahydrothiophene, N-methylimidazole and pyridine) compounds could be readily prepared in water [22].…”
Section: Synthesesmentioning
confidence: 99%
“…One equivalent each of the rhenium reagent and sodium dimethyldithiocarbamate hydrate and an excess of the neutral ligand were allowed to reflux in the solvent. It made no difference in outcome whether Re(CO) 5 3 ]Á6H 2 O [28]) was used as the reagent. Previously, we found that Re(CO) 3 L 3 + (L = NH 3 , tetrahydrothiophene, N-methylimidazole and pyridine) compounds could be readily prepared in water [22].…”
Section: Synthesesmentioning
confidence: 99%
“…In the 1800–2200 cm −1 region, unmodified lysozyme is transparent, but the Re(CO) 3 + modified crystals show ν(CO) stretching bands corresponding to e and a 1 modes (1890, 2001 and 2013 cm −1 ) resulting from the pseudo-C 3v symmetry of the facial Re(CO) 3 + unit. These bands do not correspond to those of the Re(CO) 3 (H 2 O) 3 species, which shows an a 1 band at 2036 cm −1 22 . The appearance of two a 1 bands is consistent with the presence of multiple rotamers of the Re(CO) 3 + adduct as described above.…”
mentioning
confidence: 90%
“…[60] However, the conjugated base [Re(OH)(OH 2 ) 2 -(CO) 3 ] formally appeared in a recent crystal structure. [59] Relevant numbers for mutual comparison are the pK a values. Because of the rapid (but reversible) formation of polynuclear species the pK a values were not directly accessible.…”
Section: Basic Properties Of [M(oh 2 ) 3 (Co) 3 ] + (M = Mn Tc Re)mentioning
confidence: 99%